The Konseling Pranikah: Sebuah Pendampingan Pastoral dalam Konteks Pelayanan Kristiani - Hery Budi Yosef; Vanny Miracleson Waruwu (JSSHA ADPERTISI JOURNAL, 2022)
Abstract In premarital counseling, there are practices to prepare prospective married couples for marriage. And usually this counseling practice is in the form of classes organized by the church according to the beliefs of the prospective bride and groom. The practice of premarital counseling is coaching with the intention of developing emotional maturity or other preparation, including personal ones. This research seeks to ascertain the importance of premarital counseling before entering into a holy marriage which will involve the church and be witnessed by many congregations. Through this research it will also be found that pre-marital counseling can foster a couple's relationship according to the Scriptures, and prepare them for the realm of marriage, then help grow emotionally mature, helping each couple to understand their role in marriage. Through a literature study with a biblical approach, this research draws a conclusion that marriage will go well and be solid for both bride and groom because it begins with pre-marital counseling where the church requires its congregation to go through that phase. This research seeks to find the best effort in dealing with marriage problems caused by a lack of counseling or guidance from related institutions, which is why divorces continue to increase. In this premarital counseling service, it can be given to prospective married couples with the aim that they really understand and understand the meaning of marriage that is desired by God in the Christian Family. So that their decision really becomes a married couple who are willing before God.